In vivo metabolism study of bergenin in rats by HPLC‐QTOF mass spectrometry. (21st May 2013) - Song, Haojing; Wang, Jin; Zhang, Rui; Liu, Xiaoyan; Yuan, Guiyan; Wei, Chunmin; Zhao, Wenjing; Li, Rong; Wang, Benjie; Guo, Ruichen
ABSTRACT Bergenin is the major component of Ardisia creanta sims and Rodgersia sambucifolia hemsl with many biological activities. Although bergenin has been used to treat human diseases in China for man years, there is no report regarding its metabolism. This is the first report to separate and identify the metabolites of bergenin in vivo. In the study, HPLC/Q‐TOF‐MS/MS was used to investigate the metabolites of bergenin in vivo by analyzing the rat body fluid and feces samples. Three metabolites of bergenin were finally identified by the TIC chromatograms, and the structures were also confirmed by their MS2 spectra. Copyright © 2013 John Wiley & Sons, Ltd.